Robustness Report on "Within-Firm Productivity Dispersion: Estimates and Implications," by Scott Orr (2022) - Joonkyo Hong; Davide Luparello (Institute for Replication (I4R), 2024)
In this study, we evaluate the reproducibility and replicability of Scott Orr's (2022) innovative approach for identifying within-plant productivity differences across product lines. Orr's methodology allows the estimation of plant-product level productivity, contingent upon a well-behaved pre-estimated demand system, which requires the use of carefully chosen instrumental variables (IVs) for output prices. Using Orr's STATA replication package, we successfully replicate all primary estimates with the ASI Indian plant-level panel data from 2000 to 2007. Additionally, applying Orr's replication codes to a sample from 2011 to 2020 reveals that the suggested IVs do not perform as expected.
Keywords: D22; D24; 330; Replication; Robustness; Productivity